Metabolic Fate of Jasmonates in Tobacco Bright Yellow-2 Cells - Świątek, Agnieszka (American Society of Plant Biologists, 2004)
Jasmonic acid and methyl jasmonate play an essential role in plant defense responses and pollen development. Their levels are temporarily and spatially controlled in plant tissue. However, whereas jasmonate biosynthesis is well studied, metabolic pathways downstream of jasmonic acid are less understood. We studied the uptake and metabolism of jasmonic acid and methyl jasmonate in tobacco (Nicotiana tabacum) Bright Yellow-2 suspension culture. We found that upon uptake, jasmonic acid was metabolized to its Glc and gentiobiose esters, and hydroxylation at C-11 or C-12 occurred. Free hydroxylated jasmonates were the preferential fraction of the culture medium. Upon hydrolysis of methyl jasmonate to jasmonic acid, a similar set of conversions occurs. In contrast to jasmonic acid, none of its derivatives interfere with the G2/M transition in synchronized tobacco Bright Yellow-2 cells.